Forever wars: Divided government and the termination of interventions in support of civil war governments. (May 2023) - Linebarger, Christopher; Enterline, Andrew J
Why do third-party states continue interventions in support of governments fighting civil wars even when continuing to do so appears futile from a military standpoint? To answer this question, we focus on third-party state domestic politics, theorising that institutional characteristics condition the likelihood that the third party will terminate support to a civil war government before a conflict ends. When a third-party state's legislature and executive branches are controlled by opposing political parties, the third party's executive is more likely to remain committed to an intervention in order to deny political opponents the opportunity to seize on the withdrawal as a basis for political advantage. To test this expectation, we assemble a data sample of third-party interventions in support of civil war governments during the period 1975–2009. The analysis suggests that the third-party divided government reduces the likelihood of an early termination of its support for a civil war government. Our analysis underscores the role of third-party domestic politics in understanding the dynamics of internationalised civil conflicts.